Peran Gender Santriwan dan Santriwati di Pondok Pesantren Al-Muqoddasah (Jurnal Bimbingan dan Konseling Islam, 2021)
Gender is a fundamental thing in social life, where one of the most important aspects of Gender is Gender Roles, Gender Roles are behavioral characteristics expected by society for men and women which include attitudes, attributes, behaviors and values that are followed by the local community. Changes in social condition and community conditions must also be balanced with a more open understanding of gender, especially on Gender Roles, because if there are gaps in Gender Roles, it will result in Gender discrimination. in the Adolescent Phase, individuals will want to know more about their identity and what role they should play in society. So it is necessary to understand gender roles and self-understanding in order to form gender roles that are in accordance with their gender identity. This study aims to determine the gender role orientation of santriwan and santriwati in Al Muqoddasah Islamic boarding school. This research was conducted with a quantitative descriptive approach with the survey method. The subjects of this study were 138 students. The data collection technique was carried out by using a questionnaire that was distributed offline to students in the Al Muqoddasah boarding school. The results of this study are that there are as many as 31% of subjects who have an androgynous gender role, as many as 25% of subjects have a Masculine gender role, as many as 23% of the subjects have a Feminine gender role, and as many as 21% of the subjects have an Undifferentiated gender role.